Studi Perbandingan Pembagian Harta Bersama Akibat Perceraian Antara Hukum Perdata dan Hukum Islam - Muhammad Fauzi Rais Lutfi; M Reyhan Aldabena; Berthon Jonathan (Jurnal Litigasi Amsir, 2025)
This study discusses the legal implications of dividing joint property in divorce cases under Law Number 1 of 1974 on Marriage. The main issue arises when assets such as houses or vehicles must be divided equally between spouses, which often proves difficult in practice. Using the normative legal research method based on literature review, this study emphasizes the importance of mutual agreement between the husband and wife as mandated by Article 36 of the Marriage Law. Joint property is defined as assets acquired during marriage, regardless of whose name they are registered under. To ensure clear ownership boundaries, a prenuptial or marital agreement is considered an essential legal instrument to limit or exclude the existence of joint property. Such agreements allow each party to maintain separate ownership of their assets, thereby preventing disputes and facilitating a fair and transparent division if a divorce occurs.